Association of Tumor Necrosis Factor-alpha Polymorphisms and Risk of Coronary Artery Disease in Patients With Non-alcoholic Fatty Liver Disease - Cheng, Yuting (Hepat Mon, 2015)
BACKGROUND: Cardiovascular events account for the main cause of death in patients with non-alcoholic fatty liver disease (NAFLD), and are largely influenced by genetic factors. Although multiple studies showed that tumor necrosis factor-alpha (TNF-α) polymorphisms are risk factors in the progression of NAFLD, few papers on the association of the polymorphisms and the developing coronary artery disease (CAD) in NAFLD patients have been reported. OBJECTIVES: The present study was designed to evaluate the association of TNF-α polymorphisms at residues -238 and -308, with the risk of developing CAD in Chinese patients with NAFLD. PATIENTS AND METHODS: The TNF-α polymorphisms at residues 238 and 308 were genotyped in B-type ultrasonography proven NAFLD patients with (n = 246), without (n = 247) CAD and healthy controls (n = 304), using polymerase chain reaction (PCR). Serum lipid profiles were determined using biochemical methods. Statistical analyses were performed using SPSS statistical software, version 20.0 for Mac. RESULTS: We found a significant association between TNF-α-238 guanine to alanine (GA) polymorphism and carriers of variant allele A between NAFLD patients with and without CAD (P < 0.05). Carriers of the A allele of TNF-α-238 had higher serum triglycerides (TG) and low density lipoprotein (LDL) levels in NAFLD patients with CAD (P = 0.025 and 0.001, respectively) and a higher TG level in NAFLD patients without CAD (P = 0.017), than their non-carrier counterparts. CONCLUSIONS: In the Chinese Han population that we studied, NAFLD patients who carry the TNF-α-238 GA polymorphism have an increased risk of developing CAD. Mechanisms underlying this potentially important association require further investigation.